Pendidikan Digital: Ulasan pada Google for Education - Wulan Yulian Anggini; Danang Dwi Harmoko (Neolectura, 2021)
In 2020, internet users in Indonesia reached 73.7% or as many as 196.7 million people. This data illustrates the high penetration of the internet in various aspects of people's lives. One aspect is education where all teaching activities are carried out online. This sudden and massive change poses a challenge to the Indonesian education ecosystem, including technology infrastructure. Google as the largest technology service provider in the world, including Indonesia, plays an important role. This study aims to analyze G-Edu (Google for Education) in depth, from services, applications, programs, to their use as a digital-based learning support tool, which is very much needed, especially during the current pandemic. The study used a qualitative descriptive method where the data collection process used a library research method. Based on the explanation of the research results, it can be concluded that the G-Edu service provides support for, 1) learning media, 2) learning resources, and 3) teacher self-development partners.